(untitled) (Praxis Educativa, 2012)
This papers introduces some reflections on the authors’ learning as professors after twenty years’ experience in teaching research methods and techniques to last year undergraduate students of social and cultural anthropology in the School of Natural Sciences and Museum (UNLP). Some of these reflections stem from an analysis of students’ expectations as regards the subject and which are stated by them at the very beginning of the academic year.